Polycomb subunit Pcgf2 mediates ovulation and fertility through transcriptional regulation progesterone receptor - Wang, Yibo; Wang, Wenji; Cheng, Kaixin; Geng, Kaiying; Liang, Jing; Wang, Peike; Zhang, Jiawei; Niu, Shudong; Jia, Longzhong; Zhang, Shuo; Li, Lingyu; Feng, Xiean; et al. (Frontiers in Cell and Developmental Biology, 2022)
Ovarian follicles are the fundamental structure to support oocyte development, which provides mature oocytes for offspring. This process requires granulosa cells (GCs) to respond to the midcycle surge of hormones, leading to GC proliferation and differentiation by a series of genes’ transcriptional expression changes. Epigenetic mediator, Polycomb Repressive Complex 1 (PRC1) has been reported to function in fetal ovarian development. However, its functional relevance to folliculogenesis and ovulation remains unknown. In this study, we demonstrated that GC-selective depletion of PCGF2, a key component of PRC1, led to the loss of follicles, ovulation defects, and a lengthened estrus cycle, resulting in subfertility in female mice. The expression of PCGF2 is in the GCs of growing follicles and increases after human chorionic gonadotropin (hCG) stimulation. PCGF2 bound to the promoter of the key ovulation gene progesterone receptor (Pgr) and upregulated the expression of Pgr by targeting the epigenetic modification of H2AK119ub1 after hCG surge. Consistently, the expression of downstream genes of Pgr also sharply decreased, which resulted in the follicular rupture failed and oocyte entrapped in corpus luteum in GC-specific Pcgf2 knockout mice. Together, our study identified that PCGF2 is essential for folliculogenesis and ovulation via modulating hormone receptor expression.